MT-ATP6 9035T>C Variant Causes Ataxia With Azoospermia and Apparent Anticipation in a Four-generation Kindred - Changrui Xiao; David Zhu; Jon Pryor; Sally A. Frutiger; H. Brent Clark; Hannah L. Casey; Matthew Bower; Guo-yun Yu; Xiaofei Du; Camilo Toro; Christopher M. Gomez (The Cerebellum, 2026)
Background The hereditary cerebellar ataxias are a clinically and genetically heterogeneous group of disorders characterized by progressive cerebellar degeneration leading to incoordination of gait, speech, limb, and eye movements. Hundreds of genes encoding diverse proteins underlie this family of degenerative disorders that may exhibit autosomal dominant, recessive, mitochondrial, or X-linked inheritance. Variations in clinical presentation, such as age of onset and severity, are typical of these disorders and are attributed to other genetic effects, notably repeat expansion instability. Methods In this observational study, we evaluated 45 individuals in a 5-generation kindred exhibiting features of progressive ataxia and cognitive impairment with wide-ranging ages of onset, intergenerational anticipation, diverse clinical features, and male infertility. Results The variant (m.9035 T > C) in the gene MT-ATP6 was detected in all affected individuals, and the age of onset from early childhood to the 8th decade was inversely correlated with heteroplasmy levels. Neuropsychological evaluation of affected individuals demonstrated low average/borderline overall intellectual ability and weaknesses in working memory, executive function, memory, and fine motor skills. Affected males had testicular atrophy and azoospermia. Postmortem examination revealed widespread cerebellar Purkinje cell loss. Testicular biopsy from one sterile male demonstrated a complete absence of germ cells and progenitors. Discussion This study expands the phenotypic spectrum of MT-ATP6 to include azoospermia in affected males with cerebellar ataxia. Those with low levels of heteroplasmy had mild adult-onset ataxia reminiscent of many forms of SCA. Those with high levels of heteroplasmy had early onset and suffered from the full complement of ataxia, mild cognitive impairment, and in males’ azoospermia.